2020
DOI: 10.1016/j.ecolecon.2020.106650
|View full text |Cite
|
Sign up to set email alerts
|

Trading off visual disamenity for renewable energy: Willingness to pay for seaweed farming for energy production

Abstract: Trading off visual disamenity for renewable energy: Willingness to pay for seaweed farming for energy production. Ecological Economics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For example, shading may result in adverse effects on bottom fauna, causing harmful seaweed blooms. Demel et al (2020) studied the willingness to accept disamenity caused by seaweed farms and the production of green energy. In a choice experiment conducted in the United Kingdom, the researchers found that people are willing to make this trade-off.…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…For example, shading may result in adverse effects on bottom fauna, causing harmful seaweed blooms. Demel et al (2020) studied the willingness to accept disamenity caused by seaweed farms and the production of green energy. In a choice experiment conducted in the United Kingdom, the researchers found that people are willing to make this trade-off.…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…Demel et al [ 49 ] analyze the same dataset using the simpler RPL-UC model without any interactions with the socio-demographic variables and not using responses to any attitudinal questions, finding that people are willing to use more coastline to farm seaweed in order to power more households. That is, they are willing to make a trade-off between the visual disamenity caused by the seaweed farms and producing more green energy.…”
Section: Case Studymentioning
confidence: 99%
“…Specifically, the study aims to understand the effects of food labels (RSPCA Assured and Red Tractor), cause-related marketing campaigns, and price on consumers' willingness to pay. DCEs enhance understanding of consumers' processing and evaluation of quality cues by simulating real-life purchasing situations which force consumers to make trade-offs between varying attributes (Dardanoni and Guerriero, 2021;Demel et al, 2020;Tonsor et al, 2009). In this study, the DCE incorporates both an animal welfare focused label (RSPCA Assured) as well as a national farming label (Red Tractor) and CRM on-packaging claims relating to farmers and planting meadows.…”
Section: Introductionmentioning
confidence: 99%